Detektorafsøgning ved Petersborg - Hartvig, Anders (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
The use of metal detectors and the developer funded archaeological excavations have long been separated – only rarely was the use of metal detectors incorporated as a tool on typical developer funded excavations. One example of this are the excavations at Petersborg during the period 2014 –2021 where Museum Sønderjylland used metal detectors systematically. The excavations revealed settlement evidence from the Neolithic period and Late Bronze Age, as well as a village in two phases dating to the Early and High Middle Ages. Amateur archaeologists organised rallies there in advance of the excavation campaigns, and systematic searches were carried out during the excavations. The many small finds were registered using a hand-held GPS device, and the data was subsequently plotted in MapInfo. By comparing the metal finds with other types of evidence, knowledge about the local rubbish policy as well as information about which types of metal objects the people of the village used during the Early and High Middle Ages can be gained. The incorporation of metal detectors on excavations will not only add other types of objects to the excavation results, but also improve our understanding of sites which have been identified but not yet excavated.